Gene expression analysis of Thaumatotibia leucotreta in response to the Cryptophlebia leucotreta granulovirus - Ridgeway, Jaryd Antony (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Gene expression studies provide baseline information on the interactions of insects with their environment. Despite the importance of this information, limited gene expression data are available for most insect pests, including the family Tortricidae (Lepidoptera), which includes Thaumatotibia leucotreta (Meyr), an important agricultural pest in Africa. Because T. leucotreta can be controlled successfully by a granulovirus, this system is a good model for exploring insect-virus susceptibility. The main aim of this study was to investigate gene expression of T. leucotreta in responce to virus infection. However, before pursuing this aim, two objectives required completion. First, the most suitable RNA extraction method for insects needed to be determined and second, the most suitable reference genes for qPCR for Tortricidae pests needed to be identified. Once these objectives were accomplished, the response of T. leucotreta to its granulovirus was evaluated at different temperatures and points after infection.Four RNA extraction methods, the RNeasy® Mini Kit, SV Total RNA isolation system, TRIzol® reagent, and a CTAB-based method, were compared using two beetle and two moth species, including T. leucotreta. The quality of extracted RNA was similar for all four species for all extraction methods. Based on several criteria, the best RNA extraction method was the SV Total RNA isolation system. Six candidate reference genes were evaluated for qPCR using different tissue types of T. leucotreta and two other Tortricidae pests. Additionally, reference genes were evaluated for T. leucotreta with and without its granulovirus at different temperatures. Reference gene stability was found to be dependent on species and tissue type. Overall the most suitable combination of reference genes for T. leucotreta were α-actin, arginine kinase and elongation factor 1-α.Gene expression of T. leucotreta in response to granulovirus infection at different temperatures and intervals after infection was evaluated by qPCR using 13 target genes associated with the infection process. Most genes were down-regulated after 24 and 48 h.p.i. However, after 72 h.p.i most genes were up-regulated. The same trend was observed at different temperatures, where most genes were down-regulated at 15°C and 25°C but up-regulated at 35°C. These results show that there is a dynamic gene expression response in T. leucotreta due to granulovirus infection under different conditions. Not only do these findings provide insight into the control of this tortricid pest, they also contribute further to our knowledge of insect-virus interactions.
Keywords: Gene expression; Insects -- Viruses; Tortricidae -- Viruses